2014
DOI: 10.5505/tjtes.2014.96493
|View full text |Cite
|
Sign up to set email alerts
|

Captopril protects against burn-induced cardiopulmonary injury in rats

Abstract: BACKGROUND:This study was designed to determine the possible protective effect of captopril treatment against oxidative damage in heart and lung tissues induced by burn injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…[28] In the present study, lung tissue structure was damaged by burn due to oxidative stress. Other studies have also shown that GSH level in lung tissue significantly decreased with betaine treatment after burn, [22,28,33] as was the case in current study. Antioxidant therapy is now used in several pathological conditions with oxidant stress, and results have been positive.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…[28] In the present study, lung tissue structure was damaged by burn due to oxidative stress. Other studies have also shown that GSH level in lung tissue significantly decreased with betaine treatment after burn, [22,28,33] as was the case in current study. Antioxidant therapy is now used in several pathological conditions with oxidant stress, and results have been positive.…”
Section: Discussionmentioning
confidence: 89%
“…[26,27] Another indicator for tissue injury is alteration of LDH level. [28] In their study, Wettstein and Häussinger showed that betaine decreased LDH level on perfused rat liver after ischemia and reperfusion through its cytoprotective effect. [29] In the present study, LDH level of rats with thermal injury was found to be high; however, in betaine-treated group it was significantly lower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation